EFL STUDENTS’ PREFERENCES FOR ORAL CORRECTIVE FEEDBACK IN SPEAKING INSTRUCTION - Ardhi Eka Fadilah; Mirjam Anugerahwati; Johannes A. Prayogo (Pascasarjana UM, 2017)
Abstract: This study investigates Indonesian EFL learners’ corrective feedback preferences including the timing, types of error, strategies of corrective feedback, and providers of error correction; and the relationship between foreign language anxiety and preferences for corrective feedback among students. Two hundred fifty seven EFL English department undergraduate students from two different course grades participated in the survey. The data were collected through questionnaire as the main data and interview as the supplementary data. The students’ were assigned to either a low anxiety group or a high anxiety group. The results showed that both sophomore students and freshman students agreed that student errors should be treated; freshman students and sophomore students had significantly similar opinions about perception, types, strategies, and providers of error correction.Key Words: students’ preference, corrective feedback, speaking instructionAbstrak: Penelitian ini bertujuan untuk mengungkap pilihan siswa terhadap umpan balik korektif yang termasuk waktu umpan balik korektif, tipe kesalahan umpan balik korektif, strategi umpan balik korektif, dan pemberi umpan balik korektif. Dua ratus lima puluh tujuh mahasiswa Bahasa Inggris dari dua tahun kelas yang berbeda ikut serta dalam penelitian berbentuk survey. Data kuantitatif diperoleh menggunakan kuesioner sebagai data utama dan interview sebagai data tambahan. Hasil pengolahan data menunjukkan bahwa kedua tingkat kelas siswa baik dari mahasiswa baru dan juga mahasiswa tahun kedua memiliki persamaan penilaian terhadap umpan balik korektif, mereka setuju bahwa kekeliruan segera dikoreksi; mahasiswa baru dan mahasiswa tahun kedua memberikan persamaan penilaian yang signifikan tentang persepsi, tipe, strategi, dan juga pemberi umpan balik korektif.Kata kunci: pilihan siswa, umpan balik korektif, instruksi berbicara